The Implications of Legalizing Same-Sex Marriage in Taiwan - Nadia Magdalena; Apriani A. Amenes (Papua Journal of Diplomacy and International Relations, 2021)
This article intends to examine the background of Taiwan’s legalization of same-sex marriage in 2019 and its implications for the Asian region. It argues that such legalization is not only to ensure marriage equality in Taiwan but is also likely to create a snowball effect on the regional level. This study utilizes the concept of equality to discern the struggle of same-sex couples in advocating for their right to marry. The success of Taiwan can undoubtedly proffer a new spirit for the LGBT community in the region. This study was conducted in qualitative research, while the data collected from secondary sources include relevant articles, books, and webpage on a website. This article found that Thailand, Cambodia, and Vietnam are potentially the following countries to approve same-sex marriage after Taiwan. The reasons are that they are considered open-minded countries, their track record in responding to the issue of same-sex marriage, and the struggles of non-governmental organizations, activists, the LGBT community, and pride festivals in these countries. However, some conservative, authoritarian and religious countries in Asia will not be likely to accept same-sex marriage.KEYWORDSConcept of equality; LGBT; same-sex couples; same-sex marriage; Taiwan